A CONCEPTUAL PEDAGOGICAL MODEL FOR INTEGRATING ARTIFICIAL INTELLIGENCE INTO THE SCHOOL EDUCATION SYSTEM - Koishybai, Б.Е. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
Abstract In the current digital era, many countries are widely incorporating the fundamentals of artificial intelligence (AI) into their educational systems. However, in the informatics curriculum for grades 10–11 in Kazakhstani schools, only 16 hours are allocated to the topic of AI. This limited time is insufficient for an effective integration of theory and practice, resulting in students acquiring only superficial practical skills. Currently, practical assignments are confined to the use of spreadsheet processors (Excel), which significantly hinders students from mastering modern AI tools. As a result, school graduates lack the essential knowledge and competencies required in the AI field to meet the demands of the digital age. To address these shortcomings, a new pedagogical approach is needed—one that tightly integrates theory and practice in AI education. This study aims to develop a conceptual pedagogical model that harmonizes theoretical and practical aspects of AI teaching, aligned with best international practices.